Maternal and environmental determinants of breast-milk mercury concentrations - Yalçin, S Songül; Yurdakök, Kadriye; Yalçin, Suzan; Engür-Karasimav, Defne; Coşkun, Turgay (The Turkish Journal of Pediatrics, 2010)
We aimed to evaluate the maternal factors [including dietary habits, dental care, smoking, anemia, levels of breast-milk zinc (Zn) and iron (Fe), and levels of serum selenium (Se), Zn and copper (Cu)] that influence breast-milk mercury (Hg) concentrations and to investigate whether there is any relation between Hg concentrations and infant growth and development during the exclusive breastfeeding period and in the second year of life. Forty-four healthy mother-infant pairs in the 10-20-day postpartum period were enrolled in the study. Maternal history and blood samples for hemoglobin, Fe, Fe binding capacity, ferritin, Se, Zn, and Cu and breast-milk samples for Fe, Zn and Hg were taken. Infant growth and development during the exclusive breastfeeding period and in the second year of life were followed. The mean concentration of breast-milk Hg was 3.42 +/- 1.66 microg/L. Serum Se levels were negatively correlated with milk Hg levels. Multivariate analysis revealed that active/passive smoking and offal intake during pregnancy and presence of maternal anemia had an impact on increased milk Hg concentrations. Preventive strategies for mercury exposure should include management of iron deficiency anemia, cessation of smoking exposure and proper nutrition during the pregnancy period.